2015
DOI: 10.1111/febs.13613
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of plant autoimmunity and ‘negative regulators’

Abstract: Genetics studies the structure/function of genes via the characterization of their mutant phenotypes. In plants, a readily scorable mutant phenotype comprises macroscopic lesions symptomatic of disease in the absence of pathogens. Such mutants therefore exhibit autoimmune phenotypes. Many of these mutants are considered to be associated with immunity and the corresponding genes have been described as ‘negative regulators’ of immunity and/or cell death. Pathogens deliver effectors into host cells to increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 48 publications
0
59
0
1
Order By: Relevance
“…PP2A is implicated in defence responses in Arabidopsis at the level of PAMP (pathogen‐associated molecular patterns) perception (Segonzac et al, ) and is a target of bacterial effector proteins (Jin et al, ). It is tempting to expect plant PP2A to be involved also in further downstream defence signalling by acting opposite to protein kinases and inhibiting MAPK signalling cascades, as has been found for MAPKs in mammalian cells (Asai et al, ; Junttila, Li, & Westermarck, ; Lassowskat, Bottcher, Eschen‐Lippold, Scheel, & Lee, ; Macho & Zipfel, ; Rodriguez, El Ghoul, Mundy, & Petersen, ). However, such targets of PP2A in plants still remain to be identified, and the basis for enrichment of defence genes in pme1 and lcmt1 needs further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…PP2A is implicated in defence responses in Arabidopsis at the level of PAMP (pathogen‐associated molecular patterns) perception (Segonzac et al, ) and is a target of bacterial effector proteins (Jin et al, ). It is tempting to expect plant PP2A to be involved also in further downstream defence signalling by acting opposite to protein kinases and inhibiting MAPK signalling cascades, as has been found for MAPKs in mammalian cells (Asai et al, ; Junttila, Li, & Westermarck, ; Lassowskat, Bottcher, Eschen‐Lippold, Scheel, & Lee, ; Macho & Zipfel, ; Rodriguez, El Ghoul, Mundy, & Petersen, ). However, such targets of PP2A in plants still remain to be identified, and the basis for enrichment of defence genes in pme1 and lcmt1 needs further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…They have been instrumental in assisting our studies of plant immunity. Previous reviews have highlighted lesion mimic mutants (Bruggeman et al, 2015; Rodriguez et al, 2016). Here we are focusing on Arabidopsis autoimmune mutants ( Table 1 ) and their application in studying plant immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a correct time and place is required when ETI system performs immune function (Smith et al 2014). Previous studies have demonstrated that immune resistance disorder resulted from inappropriate NB-ARC protein activation (Rodriguez et al 2015). In this study, the NB-ARC genes expression was obviously up-regulated by 91.67% in SP2 stage, and serious death was correspondingly occurred (Fig.…”
Section: Discussionmentioning
confidence: 61%